The Due Process Paradox in the New Criminal Procedure Code: Expansion of Coercive Measures and an Integrated Judicial Oversight Model in the Investigation Stage - Prastopo Prastopo; Jelli Rita; Ahmad Jaeni; Sugianor Sugianor (Jurnal Ragam Pengabdian, 2025)
The enactment of Law Number 20 of 2025 on the Indonesian Criminal Procedure Code marks a substantial transformation of investigation and coercive measures. On the one hand, the new Code strengthens suspects’ rights, broadens pretrial review, requires at least two pieces of evidence for suspect designation and several restrictions on liberty, and provides more explicit safeguards for vulnerable groups. On the other hand, the catalogue of coercive measures is expanded to include suspect designation, arrest, detention, search, seizure, interception, examination of correspondence, blocking orders, and travel bans, thus preserving a broad space for state intervention into individual liberty. This article applies normative legal research with a descriptive-prescriptive analytical character, relying on secondary legal materials through library research and employing statutory and conceptual approaches. It argues that the central problem of the new Code does not merely concern the existence of rights-protective norms, but the consistency of judicial oversight over investigative discretion. By examining Constitutional Court Decision No. 21/PUU-XII/2014, contemporary pretrial practice on suspect designation, and the oversight architecture of the new Criminal Procedure Code, this article proposes an integrated judicial oversight model based on legality, necessity, proportionality, written reasons, judicial authorization, post factum review, exclusionary rules, and effective remedies. The model is necessary to ensure that the expansion of coercive powers does not reproduce crime-control dominance, but moves toward substantive due process of law.